เบี้ยปรับและเงินเพิ่มกรณีการกำหนดราคาโอน - วิชริณี คุปตานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Currently, the Revenue Code does not include particular transfer pricing penalties. The existing provisions are ineffective to prevent related companies from conducting transfer mispricing. Meanwhile, the absence of a specific penalty-exemption provision leaves good faith taxpayers unprotected by the law. Therefore, the author aimed to study criteria for evaluation of penalties and economic concepts relating to penalties. The author also comparatively studied transfer pricing penalties of the US and South Korea in hope that the results of the study will be beneficial for amending and improving Thai tax penalties for transfer pricing issues. From the study, the author found that there are two types of penalties relating to transfer pricing. One is the penalty for failure to submit transfer pricing documentation. The other is the penalty for failure to pay tax due to mispricing. In contrast with the US and South Korea, Thailand has not legislated specific provisions for both types of penalties. Instead, the general provisions, namely, Sections 35 and 36 of the Revenue Code, are used to penalize taxpayers in case of failure to submit documentation, and Section 22 and 27 of the Revenue Code are used in the case of failure to pay. However, the application of general penalties to transfer pricing issues contradicted the criteria for evaluation of penalties which consists of fairness, effectiveness, comprehensibility and administrability. In sum, the existing penalty provisions under the Revenue Code lack consistency with the criteria for evaluation of penalties when being applied to transfer pricing cases. Therefore, the author proposes that specific transfer pricing penalty provisions be enacted based on fairness for taxpayers, effectiveness and administrability for the government, and comprehensibility for both authorities and taxpayers.